The Influence Of Performance Benefits And Work Discipline On The Performance Of The State Civil Apparatus: Empirical Study Of Demak Regency Regional Secretariat - Ina Mega Nuryati; Hikmah Hikmah (International Conference On Digital Advanced Tourism Management And Technology, 2023)
This research aims to determine the effect of performance allowances and performance discipline on employee performance. The population in this study was 120 ASN employees at the Regional Secretariat of Demak Regency. The sample size was 55 respondents based on the Slovin formula. The sampling method used was Proportionate Stratified Random Sampling and Simple Random Sampling. The data analysis used in this research is multiple linear regression.The research results show that performance allowances influence employee performance at the Demak Regency Regional Secretariat. The better the benefits provided, the better the employee's performance. Work discipline influences employee performance at the Demak Regency Regional Secretariat.